World Migration Report 2000 - International Organization for Migration (United Nations, 2000)
International migration has become a global phenomenon involving a wide range of sending, destination, and transit countries and a diverse group of migrants. This report, produced by the United Nations and the International Organization for Migration, provides an authoritative account of contemporary trends, issues, and problems in the field of international migration. It examines the scale of migration and characteristics of international migrants, the types of movements, the contributing factors and policy issues. It also presents regional country profiles examining such issues as: trends in immigration and emigration; the integration of migrants; the consequences of irregular migration; and the extent of interregional cooperation between states.